The Image of Social Life in Theodore Dreiser's Novels Such As "Jennie Gerhardt", "Sister Carrie", "American Tragedy" - Baqoyeva Muhabbat Qayumovna; Aminjonova Muattar Odiljon qizi (European Science Publishing, 2023)
This article talks about the works of the famous American writer Theodore Dreiser, the theme of social life in them, mutual problems between the characters and the society, and psychoanalytical analysis of the characters and events of the work.
Keywords: social life, artistic idea, social class, moral corruption, bourgeois America, Caroline Member, Jennie Gerhardt, Clyde Griffiths.